The Significance of Culturally Hybrid Religious Artifacts in a Multicultural Society - Sulistyani, Hapsari Dwiningtyas; Rahmiaji, Lintang Ratri; Rahardjo, Turnomo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The Cheng Ho Mosque in Surabaya is the study's main point since it is a cultural artifact with a structural layout and social objectives that combine Chinese and Islamic traditions. The Cheng Ho Mosque is a cultural object, as well as a social arena that represents hybrid culture. The cultural artifact serves as essential for understanding how social interaction takes place in an environment with symbols representing cultural hybridity. This study aims to show how Cheng Ho Mosque, as a cultural artifact, develops significance and becomes part of a cultural group's daily existence. The main theoretical framework used in this study is Cultural Identity Theory. Cultural semiotics is the research method that is being used. The study's findings suggest that the cultural semiotic frame analysis of the artifacts indicates three distinct characteristics of Surabaya's Cheng Ho Mosque: a religious place, a commercial space, and a social space. Worship activities including prayer, reading the Holy Qur'an, and recitation are all part of the interactions in the mosque's main function. The architecture of the buildings surrounding the mosque, meanwhile, was designed to reflect the business culture and network of the Chinese community in Surabaya and the area, including the use of corporate sponsors for events that are not just religious but also for general community activities including sports and gatherings of the Surabaya Chinese community. The Cheng Ho Mosque is an artifact that represents the distinctive features of Chinese Muslims as a subculture.